2023
DOI: 10.1007/s11136-023-03414-0
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life before and during the COVID-19 pandemic in Switzerland: a cross-sectional study

Abstract: Introduction The COVID-19 pandemic forced people to give up their daily routines and adjust to new circumstances. This might have affected health-related quality of life (HRQOL). We aimed to compare HRQOL during the first COVID-19 wave in 2020 to HRQOL before the pandemic and to identify determinants of HRQOL during the pandemic in Switzerland. Methods We conducted a cross-sectional online survey during the pandemic (between May and July 2020; CoWELL sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
2
3
0
Order By: Relevance
“…Furthermore, mental HRQOL increased with age, while physical HRQOL deteriorated with increasing age. Interestingly, mental HRQOL was higher when living with a partner without responsibility for children, which aligns with findings from the Norwegian national survey [ 71 , 73 ]. The findings from the Swiss [ 73 ] study is only partly consistent with our findings that gender differences are significant in both mental and physical HRQOL.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Furthermore, mental HRQOL increased with age, while physical HRQOL deteriorated with increasing age. Interestingly, mental HRQOL was higher when living with a partner without responsibility for children, which aligns with findings from the Norwegian national survey [ 71 , 73 ]. The findings from the Swiss [ 73 ] study is only partly consistent with our findings that gender differences are significant in both mental and physical HRQOL.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, mental HRQOL was higher when living with a partner without responsibility for children, which aligns with findings from the Norwegian national survey [ 71 , 73 ]. The findings from the Swiss [ 73 ] study is only partly consistent with our findings that gender differences are significant in both mental and physical HRQOL. The selected group might explain the differences in the current study, where all participants are parents of adolescents, and the stress of parenting combined with living through the COVID-19 pandemic can be explanatory factors.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Lockdowns and increased levels of distress due to COVID-19 have a significant impact on HRQoL. A Swiss general population study found that physical HRQoL significantly increased while mental HRQoL significantly decreased during the COVID-19 pandemic [ 33 ]. By contrast, in a Spanish population, both components, physical and mental, were significantly lower during the pandemic [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has affected sexual health at the individual, systemic, and societal levels [13]. Studies, including meta-analyses, have shown that during the pandemic, the general population noted a decrease in the assessment of female sexual functioning, including satisfaction, arousal, orgasm, and pain measured by Female Sexual Function Index (FSFI) [10,[14][15][16][17][18][19]. Even though numerous studies analyzing the effects of the pandemic on women's sexual function in the general population have been conducted, there is no clear evidence that the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection causes sexual dysfunction through an organic mechanism in women.…”
Section: Introductionmentioning
confidence: 99%